2019
DOI: 10.1016/j.colsurfb.2019.03.071
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulated functionalized stereocomplex PLA particles: An effective system to support mucolytic enzymes

Abstract: In this work, the preparation of a novel enzyme carrier based on a polymer multicomponent system was assessed. Indeed, the design of the above system considered several issues that are the need of applying a biodegradable polymer carrier, characterized by a nanometric dimension, thus suitable to diffuse into the dense mucus structure, with functionalities capable of interacting/reacting with enzymes but resistant to enzymatic degradation. The particles were prepared from solutions containing equimolar amount o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 68 publications
2
18
0
Order By: Relevance
“…60 In the current experiment, we have focused our attention on the quantitative s-SNOM imaging of a specific class of PMCs, namely biopolymeric capsules that can self-degrade in a controlled fashion upon the interaction of an entrapped proteolytic enzyme with the PMC walls. This experiment extends previous recent work, 34 where it was shown by confocal microscopy and AFM how enzymes loaded inside such microcapsules disrupt the microcapsules shell. The investigation and evaluation of the degradative process play a pivotal role for the design of efficient delivery systems; however, considering the dimensions of the microcapsules, and the scale at which degradation cues occur, this process is impossible to be optically investigated in detail with diffraction-limited techniques.…”
Section: Resultssupporting
confidence: 91%
“…60 In the current experiment, we have focused our attention on the quantitative s-SNOM imaging of a specific class of PMCs, namely biopolymeric capsules that can self-degrade in a controlled fashion upon the interaction of an entrapped proteolytic enzyme with the PMC walls. This experiment extends previous recent work, 34 where it was shown by confocal microscopy and AFM how enzymes loaded inside such microcapsules disrupt the microcapsules shell. The investigation and evaluation of the degradative process play a pivotal role for the design of efficient delivery systems; however, considering the dimensions of the microcapsules, and the scale at which degradation cues occur, this process is impossible to be optically investigated in detail with diffraction-limited techniques.…”
Section: Resultssupporting
confidence: 91%
“…Despite these advantages, many challenges remain for the application of sc-PLA as a drug carrier, including inferior encapsulation efficiency, low stability of hydrophilic drugs and proteins, and the burst release phenomenon. To resolve these issues, various strategies, such as polymerization, self-assembly, surface modification, and polymer grafting, have been studied [ 13 , 14 , 15 , 16 , 17 ]. This review discusses various synthesis and processing methods for the application of sc-PLA as a drug and molecular carrier, and it suggests future directions to stimulate the application of sc-PLA with therapeutic molecules in drug delivery systems and biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
“…In animal studies, proteases were demonstrated to digest LbL films constructed with dextran and poly(Larginine). Another study took advantage of an enzyme which was put inside LbL films with poly(L-lactide) and poly(D-lactide) to adjust their degradation time [210].…”
Section: Biology Induced Releasementioning
confidence: 99%